Caracterização de quitinases expressas em diferentes estágios de desenvolvimento da formiga cortadeira Atta sexdens - Silva, Izabella Rodrigues Fonseca da (Universidade Federal de São Carlos, 2025)
Chitinases (E.C.3.2.1.14) are enzymes that degrade chitin, a homopolysaccharide found in the cell wall of fungi, in the exoskeleton of insects, and in other lower eukaryotic organisms. Due to their enzymatic role in chitin hydrolysis, insect chitinases play essential functions during molting, cell proliferation, immune defense, and also in obtaining nutrients. This study aimed to isolate and characterize chitinases expressed by the leaf-cutter ant Atta sexdens in two distinct stages of the life cycle: pupa (Quit-ASP) and adult/worker (Quit-ASOA). The extraction of chitinases was performed by macerating 400 mg of ants in 2 mL of 50 mM sodium acetate buffer pH 5.0 containing 0.1% Tween 20. After centrifugation, the supernatant was subjected to three purification steps: precipitation with ammonium sulfate, anion exchange chromatography, and molecular exclusion. The optimal pH and temperature for activity were determined using colloidal chitin as a substrate. Quit-ASOA, which showed an apparent molecular mass of 70 kDa by SDS-PAGE, demonstrated high thermal stability. Furthermore, it demonstrated optimal activity at pH 6.0 and an optimal temperature of 50 °C. Quit-ASP, in turn, showed an optimal pH of 9.0 and an optimal temperature of 55 °C. Both chitinases had their activity increased in the presence of certain metal ions. Mass spectrometry analysis of the primary structure of Quit-ASOA indicated the presence of a chitin-binding domain. This study demonstrated that A. sexdens expresses different chitinases in the pupal and adult stages.
Characterization of chitinases expressed in different developmental stages of the leaf-cutter ant Atta sexdens
Keywords: Quitinase; Atta sexdens; Pupa; Operária; CIENCIAS EXATAS E DA TERRA::QUIMICA; 15. Vida Terrestre